The association between body mass index and recovery from post-traumatic stress disorder after the nuclear accident in Fukushima - Nagai, Masato (Sci Rep, 2021)
Post-traumatic stress disorder (PTSD) and obesity share common risk factors; however, the effect of obesity on recovery from PTSD has not been assessed. We examined the association between body mass index (BMI) and recovery from PTSD after the Great East Japan Earthquake. We analyzed 4356 men and women with probable PTSD aged ≥ 16 years who were living in evacuation zones owing to the radiation accident in Fukushima, Japan. Recovery from probable PTSD was defined as Post-traumatic Stress Disorder Checklist-specific scores < 44. Using Poisson regression with robust error variance adjusted for confounders, we compared the prevalence ratios (PRs) and 95% confidence intervals (CIs) for this outcome in 2013 and 2014. Compared with point estimates for normal weight (BMI: 18.5–24.9 kg/m(2)), especially in 2013, those for underweight (BMI: < 18.5 kg/m(2)) and obesity (BMI: ≥ 30.0 kg/m(2)) tended to slightly increase and decrease, respectively, for recovery from probable PTSD. The multivariate-adjusted PRs (95% CIs) for underweight and obesity were 1.08 (0.88–1.33) and 0.85 (0.68–1.06), respectively, in 2013 and 1.02 (0.82–1.26) and 0.87 (0.69–1.09), respectively, in 2014. The results of the present study showed that obesity may be a useful predictor for probable PTSD recovery. Obese victims with PTSD would require more intensive support and careful follow-up for recovery.